Technology Acceptance Model and Corporate Governance: Reducing Fraud in E-Reimbursement Systems - Farnets, Careyi; Garce, Croskey; Smiht, Chen (Inovasi Analisis Data, 2024)
Purpose: Drawing on the context of Australia, this research investigates the complex interplay of corporate governance, trust in e-reimbursement systems, and employee intention to truthfully disclose information.Method: Using an online quantitative survey designed for Australian staff members who utilize e-reimbursement systems, the study investigates how perceived usefulness, perceived ease of use, perceived security, and corporate governance affect trust and disclosure intention through structural equation modeling.Findings: To this end, the study reveals the role of several factors related to corporate governance influencing trust and unethical behavior in e-reimbursement.” The governance structures in place that ensure transparency, accountability, and ethical conduct go a long way in establishing trust in these systems. The results indicate that having a corporate governance framework can create an environment where employees are comfortable with their disclosures and instill them with honesty and integrity.Novelty: This study advances the literature by integrating the concepts of technology adoption, corporate governance and ethics in the digital age. Through this novel theoretical insight, the study explores how governance mechanisms could moderate the relationship between trust in e-reimbursement systems and the intention to share (or not share) information, providing a new lens to understand how traditional views on organizational behavior can be expanded through the lens of theory.Implications: The study's implications are significant for leading organizations in Australia and worldwide. It highlights the need for strong corporate governance frameworks that are in place alongside digital transformation efforts to ensure employees feel safe and incentivized to disclose any information in good faith. In addition, the results imply that future studies should investigate long-term studies that follow employee behaviour over time as governance and technologies evolve